Analisis Teknik Penerjemahan Film (Subtitling) Queen of Katwe - Siboro, Juli Andriana (Jurnal Penerjemahan, 2022)
This article discusses the techniques utilized for the film subtitling of “Queen of Katwe”. Its objectives are to identify and analyze the techniques applied by the translator in the film subtitling. This study used the descriptive qualitative method. Its data were collected by means of content analysis technique. The results of the study show that several techniques are applied by the translator for the film subtitling of “Queen of Katwe”. They include adaptation, amplification, borrowing, calque, compensation, discursive creation, established equivalent, generalization, linguistic amplification, linguistic compression, literal translation, modulation, particularization,reduction, transposition, and variation techniques. Meanwhile, substitution and description techniques are not applied by the translator for the film subtitling. Keywords: Techniques, subtitling, Queen of Katwe